2011
DOI: 10.1074/jbc.m110.158675
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin/Nuclear Factor of Activated T Cells and MAPK Signaling Induce TNF-α Gene Expression in Pancreatic Islet Endocrine Cells

Abstract: Cytokines contribute to pancreatic islet inflammation, leading to impaired glucose homeostasis and diabetic diseases. A plethora of data shows that proinflammatory cytokines are produced in pancreatic islets by infiltrating mononuclear immune cells. Here, we show that pancreatic islet ␣ cells and ␤ cells express tumor necrosis factor-␣ (TNF-␣) and other cytokines capable of promoting islet inflammation when exposed to interleukin-1␤ (IL-1␤). Cytokine expression by ␤ cells was dependent on calcineurin (CN)/nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 89 publications
1
45
0
Order By: Relevance
“…Through exposure to pro-inflammatory cytokines and other stimuli, beta cells can synthesise IL1β and TNFα [7,9]. This occurs in part through ROS-mediated activation of MAPKs (ERK, JNK and p38), which in turn activate NFκB with subsequent induction of IL1β.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through exposure to pro-inflammatory cytokines and other stimuli, beta cells can synthesise IL1β and TNFα [7,9]. This occurs in part through ROS-mediated activation of MAPKs (ERK, JNK and p38), which in turn activate NFκB with subsequent induction of IL1β.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes is a progressive inflammatory state, characterised by abnormally elevated islet levels of proinflammatory cytokines, such as IL1β and TNFα, which have been demonstrated to suppress beta cell function and mass [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Although an inflammatory reaction and oxidative stress have been found to be strongly associated with myocardial damage, the exact signaling pathways involved in the perpetuation of myocardial damage, LV dysfunction, and cardiac remodeling remain unclear. Previous studies have shown that the MAPK pathway is frequently up-regulated by environmental and oxidative stresses as well as inflammatory and cytokine stimulations, thereby leading to cell apoptosis and inflammatory cytokine production [12][13][14][15][16][17] . On the other hand, the Akt signaling pathway has been shown to be an essential contributor to vascular smooth muscle cell migration and proliferation in response to mechanical stress 18) .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the MAPK pathway is activated in response to environmental and oxidative stresses, cellular proliferation and apoptosis, as well as inflammation and cytokine stimulation [12][13][14][15][16][17] . Another kinase signaling pathway, the PI-3 kinase/Akt signal pathway, has been shown to participate in the modulation of vascular smooth muscle cell migration and proliferation in response to mechanical stress 18) ; however, whether MAPK and PI-3 kinase/Akt signaling pathways are associated with the inflammatory response, generation of oxidative stress, increased infarct size and cardiac remodeling after AMI is currently unclear.…”
Section: Animal Model Of Ami and Rationale Of Tacrolimus Dosage For Ementioning
confidence: 99%
“…Il-1b have been previously shown to induce TNF expression in endocrine cells (a and b cells) via calcineurin/nuclear factor of activated T cells (NFAT) and MAPK Signaling. 38 Furthermore, our earlier reports on adipose tissue 39 and mesenchymal stem cells (bone marrow) 40 have substantiated inflammation to play a central role in obesity with IR in WNIN mutant rat. We also found increased CD11b positive cells (macrophage marker) localized in islets as compared to lean littermates and controls.…”
Section: E998099-6mentioning
confidence: 99%